2007
DOI: 10.1261/rna.372307
|View full text |Cite
|
Sign up to set email alerts
|

The eIF4G–homolog p97 can activate translation independent of caspase cleavage

Abstract: The eukaryotic initiation factor (eIF) 4G family plays a central role during translation initiation, bridging between the 59 and 39 ends of the mRNA via its N-terminal third while recruiting other factors and ribosomes through its central and C-terminal third. The protein p97/NAT1/DAP5 is homologous to the central and C-terminal thirds of eIF4G. p97 has long been considered to be a translational repressor under normal cellular conditions. Further, caspase cleavage liberates a p86 fragment that is thought to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…4A). Because even total blockade of eIF4E-eIF4G interactions would not be expected to block all protein synthesis, this level of protein synthesis reduction was not surprising (5,17,18). However, our results are interesting in the context of previous studies because we found significant memory impairments at levels of protein synthesis blockade below those (either presumed or measured) in previous studies using other protein synthesis inhibitors (12,13,19).…”
Section: Resultssupporting
confidence: 53%
“…4A). Because even total blockade of eIF4E-eIF4G interactions would not be expected to block all protein synthesis, this level of protein synthesis reduction was not surprising (5,17,18). However, our results are interesting in the context of previous studies because we found significant memory impairments at levels of protein synthesis blockade below those (either presumed or measured) in previous studies using other protein synthesis inhibitors (12,13,19).…”
Section: Resultssupporting
confidence: 53%
“…Cap-independent translation is often upregulated when cap-dependent translation is reduced. However, full-length NAT1 is present on active polysomes in unstressed cells (Nousch et al 2007), indicating a role for this factor under normal conditions. Indeed, RNAi against NAT1 during mitosis results in apoptosis, due to translation deficits in BCL-2 and CDK1 production (Marash et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…65 FXR1a-microRNP interacts with p97/DAP5, a non-canonical translation factor that brings in eIF3-40S ribosome subunit in place of eIF4G. [103][104][105][106][107][108][109][110][111][112][113] FXR1a-microRNP also interacts with PARN that binds mRNA 5 0 caps in G0 in place of eIF4E, thus connecting p97-FXR1a-microRNP that is recruited to the 3 0 UTR, with the 5 0 cap to replace the canonical 5 0 -3 0 eIF4E-eIF4G-PABP link. 31 These alternate cap binding and ribosome recruitment factors promote specialized translation of specific poly(A) shortened mRNAs associated with FXR1a-microRNP in quiescent conditions, where canonical translation is reduced.…”
Section: Canonical Translation Mechanismmentioning
confidence: 99%
“…[103][104][105][106] P97 lacks eIF4E and PABP binding sites, but possesses a similar eIF3 binding site to that of canonical translation factor eIF4G, which can recruit eIF3 and thereby, 40S ribosome subunits to initiate translation. 105,107 P97 has been shown to mediate cap independent, IRES driven translation during cellular stress and specific conditions [107][108][109][110][111][112][113] where p97 is recruited via mRNA interactions. P97 mediates cap dependent alternative translation in quiescent conditions, where canonical translation factor eIF4G-that brings in the 40S ribosome subunit to initiate translation-cannot be recruited due to interference with the cap complex by active 4EBPs.…”
mentioning
confidence: 99%